2018
DOI: 10.3389/fpsyt.2018.00088
|View full text |Cite
|
Sign up to set email alerts
|

Cue-Induced Brain Activation in Chronic Ketamine-Dependent Subjects, Cigarette Smokers, and Healthy Controls: A Task Functional Magnetic Resonance Imaging Study

Abstract: BackgroundObservations of drug-related cues may induce craving in drug-dependent patients, prompting compulsive drug-seeking behavior. Sexual dysfunction is common in drug users. The aim of the study was to examine regional brain activation to drug (ketamine, cigarette smoking) associated cues and natural (sexual) rewards.MethodsA sample of 129 [40 ketamine use smokers (KUS), 45 non-ketamine use smokers (NKUS) and 44 non-ketamine use non-smoking healthy controls (HC)] participants underwent functional magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We included 16 studies in our review, totaling 440 chronic ketamine users with a mean ketamine use of 2-9.7 years and 2.4 grams per day, compared to 259 drug-free controls and 44 poly-drug controls. Five studies were based on the same sample (Liao et al, 2010(Liao et al, , 2011(Liao et al, , 2012(Liao et al, , 2016(Liao et al, , 2018. The included studies described structural gray matter and white matter differences, differences in brain functionality and differences in neurotransmitter receptor binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 16 studies in our review, totaling 440 chronic ketamine users with a mean ketamine use of 2-9.7 years and 2.4 grams per day, compared to 259 drug-free controls and 44 poly-drug controls. Five studies were based on the same sample (Liao et al, 2010(Liao et al, , 2011(Liao et al, , 2012(Liao et al, , 2016(Liao et al, , 2018. The included studies described structural gray matter and white matter differences, differences in brain functionality and differences in neurotransmitter receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…Because of these heterogenous results, we could not perform a quantitative bias analysis. Bias could play a role, since the 5 studies by Liao et al (2010Liao et al ( , 2011Liao et al ( , 2012Liao et al ( , 2016Liao et al ( , 2018 were based on the same sample. For that reason, we compared the results if four of these five studies were left out of the analysis, to the situation in which all five studies were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rsFC can provide a valuable tool for exploring large-scale brain networks and their interactions and identifying the neural circuit disorders behind SUD [ 121 , 123 ]. Using fMRI, we found that ketamine could significantly increase neuronal activity, especially in the PFC, anterior cingulate cortex, precuneus, and precentral frontal gyrus [ 99 , 100 , 101 ]. Chronic ketamine use can also alter rsFC, especially in the thalamus, basal ganglia, and higher cortex [ 97 ].…”
Section: Molecular Mechanism Of Non-opioid Anesthetic Drug Addictionmentioning
confidence: 99%
“…Imaging studies found that cannabis, cocaine, and heroin users all showed abnormal activation in the anterior insula, DLPFC, and inferior parietal lobe compared with healthy control participants using a cue-induced craving task (Zilverstand et al ., 2018 ). One study found ketamine addicts exhibited increased activation in the anterior cingulate gyrus and precuneus than healthy control when exposed to ketamine-related clips, while the anterior central frontal gyrus was mainly activated under smoking-related cues (Liao et al ., 2018a ).…”
Section: Introductionmentioning
confidence: 99%